2018
DOI: 10.1080/10428194.2018.1492122
|View full text |Cite
|
Sign up to set email alerts
|

Resminostat in patients with relapsed or refractory Hodgkin lymphoma: results of the phase II SAPHIRE study

Abstract: This open-label, single-arm phase II study examined efficacy, safety, pharmacokinetics, and biomarkers of histone deacetylase (HDAC) inhibitor resminostat in patients with relapsed or refractory Hodgkin lymphoma. Thirty-seven heavily pretreated patients received 600 (19 patients) or 800 mg (18 patients) oral resminostat daily for the initial 5 days of 14-day treatment cycles. Objective response rate (ORR) (primary) was 34% reaching disease control in 54% patients. Most patients (69%) showed reduced tumor size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Recent advances in basic research have revealed molecular pathogenesis of cHL (Figure 6) 101,102 leading to the clinical development of several targeted small molecules (Table 6). [103][104][105][106][107][108][109][110][111][112] However, the development of these small molecules fell out of favor because of their moderate efficacy with singleagent use. Currently, the combination of BV and/or immune checkpoint inhibitors with small molecules is being tested in early phase trials.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in basic research have revealed molecular pathogenesis of cHL (Figure 6) 101,102 leading to the clinical development of several targeted small molecules (Table 6). [103][104][105][106][107][108][109][110][111][112] However, the development of these small molecules fell out of favor because of their moderate efficacy with singleagent use. Currently, the combination of BV and/or immune checkpoint inhibitors with small molecules is being tested in early phase trials.…”
Section: Discussionmentioning
confidence: 99%
“…Previously tested in Phase I or II studies in patients with hepatocellular carcinoma, Hodgkin lymphoma, biliary tract and pancreatic cancer, and non‐small cell lung cancer 86,92,93,95 …”
Section: Advanced Diseasementioning
confidence: 99%
“…The 110 mg dose level provided slightly better ORR, but was not well tolerated, with two deaths potentially related to treatment, while the results of entinostat and resminostat were less encouraging. [195][196][197] JAK inhibitors could be active in HL through the blockade of the JAK-STAT pathway. Unfortunately, the clinical results of pacritinib and ruxolitinib were heterogenous and rather disappointing (Table 3).…”
Section: Brentuximab Vedotin As Salvage Therapy For Relapsed/refractomentioning
confidence: 99%
“…Several novel agents had shown promising results, but their development was delayed or stopped with the appearance of the impressive results obtained with BV and checkpoint inhibitors. The potential role of such targeted agents in rr-cHL, including mTOR inhibitors, lenalidomide, histone deacetylase inhibitors (HDACi), and JAK inhibitors, as well as inhibitors of the B-cell receptor (BCR) pathway, 189210 and details of major clinical trials of these agents are summarized in Table 3.…”
Section: Third-line Therapy and Beyondmentioning
confidence: 99%
See 1 more Smart Citation